2022
DOI: 10.1097/crd.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome Type 3 Review

Abstract: The management of patients with complex comorbidity involving several organ systems can use an approach focused on each organ system independently or can use an approach trying to integrate various injuries and dysfunction into a single syndrome. Cardiorenal syndromes can develop with an initial injury to either the heart or kidney and then sequential involvement of the second organ. This can occur acutely or chronically. Cardiorenal syndrome type 3 is defined by acute renal injury with subsequent cardiac inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In fact, inefficient post-renal repair can lead to long-lasting morbidity and even mortality due to renal and non-renal causes [ 33 ]. Many studies have shown that patients after kidney transplantation surgery develop ischemic heart disease, congestive heart failure and left ventricular hypertrophy [ 6 , 15 ]. In the present study, we explored the connectivity between renal IR surgery repair and recovery with cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, inefficient post-renal repair can lead to long-lasting morbidity and even mortality due to renal and non-renal causes [ 33 ]. Many studies have shown that patients after kidney transplantation surgery develop ischemic heart disease, congestive heart failure and left ventricular hypertrophy [ 6 , 15 ]. In the present study, we explored the connectivity between renal IR surgery repair and recovery with cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the distant cardiac effects of renal IRI remain to be fully elucidated, but they are likely to involve a complex interplay of systemic inflammation, neurohormonal activation, mitochondrial dysfunction, oxidative stress, and endothelial dysfunction [ [14] , [15] , [16] ] [ [14] , [15] , [16] ] [ [14] , [15] , [16] ]. Among these pathological mediators, mitochondrial dysfunction is generally overlooked despite its potential to be involved in the crosstalk between the pathologies and coordinate them all due to the difficulty in mitochondrial health assessment as compared to other mentioned parameters [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We present a case of progressive renal infarction caused by chronic thrombosis of bilateral aortic-iliac stenting in place for more than 10 years. A complex clinical picture, complicated by type 3 cardio-renal syndrome [ 5 ], caused a delay in diagnosis. At the time of the definitive diagnosis, there was no longer indication for reperfusion therapy, and the patient needed transitory renal function replacement therapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various pathophysiological processes contribute to the occurrence and development of CRS-3. Fluid retention during acute kidney injury can lead to pulmonary edema 5 . Electrolyte disturbances such as hyperkalemia can cause arrhythmias and even cardiac arrest 6 .…”
Section: Introductionmentioning
confidence: 99%